Modern concepts of scleral buckling in the treatment of rhegmatogenous retinal detachment - V.N. Kazaykin; A.V. Lizunov; M.A. Lipina (Офтальмохирургия)
Relevance. Rhegmatogenous retinal detachment (RRD) is a serious problem of modern ophthalmology, leading to an irreversible decrease in vision and, in extreme cases, to its loss. The prevalence of RRD according to various sources varies from 8.9 to 24.4 cases per 100,000 population, in most cases these are patients of working age – 84–89%. Purpose. To analyze the role of extrascleral buckling in treatment of rhegmatogenous retinal detachment. Material and methods. In the search for materials, open electronic databases Google and Google Scholar, PubMed, Embase, MEDLINE and Web of Science were used, 58 sources were analyzed up to 2023. Results. At the beginning of the 20th century, retinal detachment irreversibly led to blindness, but starting from the late 1920s, the first surgical techniques appeared that made it possible to successfully restore its anatomical position. Extrascleral buckling (ESP) became an established treatment for retinal detachment with a long-term success rate of 93%. The vast majority of rebleeds ultimately continued to occur due to missed tears, inaccurate buckling, or inadequate retinopexy. Much has changed since the development in 1971 by R. Machemer of a device for vitrectomy through the pars plana, as a result of which the surgical focus shifted towards the vitreal cavity. Conclusion. Scleral buckling still remains an effective surgical intervention in a certain group of patients with retinaldetachment, including combined operations, and its undoubted advantage is the unpretentiousness of technical support.